A novel view of the transcriptome revealed from gene trapping in mouse embryonic stem cells - Roma, Guglielmo; Cobellis, Gilda; Claudiani, Pamela; Maione, Francesco; Cruz, Pedro; Tripoli, Gaetano; Sardiello, Marco; Peluso, Ivana; Stupka, Elia (Genome Research, 2007)
Embryonic stem (ES) cells are pluripotent cell lines with the capacity of self-renewal and the ability to differentiate into specific cell types. We performed the first genome-wide analysis of the mouse ES cell transcriptome using ∼250,000 gene trap sequence tags deposited in public databases. We unveiled >8000 novel transcripts, mostly non-coding, and >1000 novel alternative and often tissue-specific exons of known genes. Experimental verification of the expression of these genes and exons by RT-PCR yielded a 70% validation rate. A novel non-coding transcript within the set studied showed a highly specific pattern of expression by in situ hybridization. Our analysis also shows that the genome presents gene trapping hotspots, which correspond to 383 known and 87 novel genes. These “hypertrapped” genes show minimal overlap with previously published expression profiles of ES cells; however, we prove by real-time PCR that they are highly expressed in this cell type, thus potentially contributing to the phenotype of ES cells. Although gene trapping was initially devised as an insertional mutagenesis technique, our study demonstrates its impact on the discovery of a substantial and unprecedented portion of the transcriptome.